FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU JUMANTIK DALAM SISTEM KEWASPADAAN DINI DEMAM BERDARAH DENGUE DI KELURAHAN SENDANGMULYO - Tegar Lyana Pangestika; Kusyogo Cahyo; Besar Tirto Husodo; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
In 2014 and 2016, City of Semarang was still ranked number 1 in highest death caused by DHF in Central Java. Until the 27th week of 2016, there were 1525 cases of DHF and 29 deaths by DHF recorded. IR in Semarang City until September 2016 was recorded 120.04/100.000 populations. Jumantik Cadre that have a role as Larva Observer which is a form of early caution from DHF. This study aims to determine the factors that affect the jumantic cadres in the system of early awareness of DHF. The type of this research is a quantitative research with cross sectional approach. By using random sampling technique, got sample 71 larva observer cadres were obtained in Sendangmulyo villages. Some of the respondents have a good behavior in DHF early caution system (54,9%). The result of the chi square test shows that age (p=0,008), attitude towards early caution behavior (p=0,001), support from health workers (p=0,015), and support from government villages (p=0,004) variables are related significantly towards larva observer behavior in DHF early caution system, whereas last education (p=0,785), occupation (p=1,000), span as larvae watch (p=0,454), knowledge about preventing and controlling DHF (p=1,000), access to prevention of DHF counseling (p=0,090), larva monitoring infrastructure (p=0,277), family support (p=0,563), and population support (p=0,782) variables are not related significantly towards larva observer behavior in DHF early caution system. The result from logistic regression test shows that from all variable, the one that has the most affect is attitude towards early caution system DHF (p=0,010) with 6,159 OR score.